Gender Differences for the Prevalence and Risk Factors of Workplace Violence Among Healthcare Professionals in Shandong, China - Sun, Long; Zhang, Wen; Qi, Fei; Wang, Yani (Frontiers in Public Health, 2022)
Background: Workplace violence (WPV) against healthcare professionals (HPs) has been recognized as an important occupational health and societal problem in the world. Many studies were also conducted to explore the prevalence, risk factors, and adverse outcomes of WPV against HPs. Although the gender differences for the prevalence and risk factors of WPV against HPs have been implied in many studies, less studies were conducted to explore the gender differences for WPV against HPs, especially in China. In this study, we aim to analyze the gender differences for the prevalence and risk factors of WPV against HPs in Shandong, China. Methods: This study was conducted among HPs with a cross-sectional design. WPV, social-demographic variables, occupational characteristics, physical disease, social support, and depression were evaluated for the participated HPs. The prevalence and risk factors of WPV among male healthcare professionals (MHPs) and female healthcare professionals (FHPs) were analyzed in this study. Student t-tests, one-way analysis of variance (ANOVA), and logistic regressions were performed to test the associated factors of WPV among MHPs and FHPs. Results: The prevalence of WPV among MHPs and FHPs was 61.4% and 48.8%, respectively. Being silence was the most common method to response to WPV among MHPs (52.3%) and FHPs (59.2%). For MHPs, the associated factors of WPV were master degree (OR=2.20, P<0.05), bachelor degree (OR=2.49, P<0.001), lower income level (OR=1.81, P<0.05), manager (OR=1.81, P<0.05), and depression (OR=1.05, P<0.001). For FHPs, the associated factors of WPV were master degree (OR=1.58, P<0.05), more working hours per week (OR=1.02, P<0.001), and depression (OR=1.05, P<0.001). Conclusion: The prevalence of WPV among MHPs was higher than FHPs, and the associated factors for WPV against HPs were also different among MHPs and FHPs. The findings remind us that some gender specific interventions are need to control WPV against HPs.